(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores how language, specifically through conceptual metaphors, encodes and reinforces gender stereotypes within society. Conceptual metaphors serve as linguistic devices that shape perceptions of gender by associating specific traits and behaviors with male and female identities. Research indicates that certain metaphorical source domains—such as BUILDING, COMPETITION, and WAR—are perceived as masculine, while others like JOURNEY and PLANT are viewed as feminine. This dichotomy reflects societal norms and expectations surrounding gender roles.Furthermore, studies reveal that the use of gender metaphors can significantly influence how individuals are perceived in various contexts, such as politics and business. For instance, women who adopt masculine metaphors often face criticism for being overly aggressive, while their male counterparts are not subjected to the same scrutiny. The implications of these metaphorical associations extend to everyday language, where conventional metaphors perpetuate gender hierarchies and reinforce dominant ideologies regarding masculinity and femininity. Overall, the examination of gender stereotypes in conceptual metaphors highlights the intricate relationship between language, culture, and social identity, suggesting that metaphors not only reflect but also shape societal attitudes towards gender.